Use Of Special Knowledge During The Investigation Of Knowingly False Testimony Of The Witness And The Victim - Romanauskas, Kristina (Archives of Criminology and Forensic Sciences, 2023)
Fair and objective justice requires compliance by all its participants with legally established principles. At the same time, in law enforcement practice there are cases of falsification of evidence, which is caused by various circumstances, and motivational factors that are guided by the participants in the process, in particular, the witness and the victim. That is why similar acts are criminalized, and the scientific community has an updated task to develop substantiated recommendations for improving the quality of investigations of similar facts. Taking into account the significant importance of special knowledge in similar criminal proceedings, which is evidenced by the analysis of court practice, the purpose of the article is defined as the clarification of typical forms of special knowledge used during the pre-trial investigation of knowingly false statements by witnesses and victims, the specifics of their implementation. Based on the results of the research, it was determined that the appointment of a forensic handwriting examination, a forensic psychiatric examination, a forensic psychological examination, in particular with the use of a polygraph, a forensic telecommunications examination, and less often a technical examination of a document is typical. Each of the outlined forensic examinations has its specifics that need to be considered. Prospects for further scientific research are outlined.